2019
DOI: 10.1002/asia.201901442
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Tandem Reaction of Functionalized Arylacetonitriles with Arylboronic Acids in 2‐MeTHF: Eco‐Friendly Synthesis of Aminoisoquinolines and Isoquinolones

Abstract: The first example of the nickel-catalyzed tandem addition/cyclization of 2-(cyanomethyl)benzonitrilesw ith arylboronic acids in 2-MeTHF has been developed, which provides the facile synthesis of aminoisoquinolines with good functional group tolerance under mild conditions. This chemistry has also been successfully appliedt ot he synthesis of isoquinolones by the tandemr eaction of methyl 2-(cyanomethyl)benzoates with arylboronic acids. The use of the biobased and green solvent2 -MeTHF as the reaction medium ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…A similar type of strategy was reported recently by Zhen et al. to access aminoisoquinolines and isoquinolones under Nickel‐catalyzed reaction conditions [158] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 78%
See 1 more Smart Citation
“…A similar type of strategy was reported recently by Zhen et al. to access aminoisoquinolines and isoquinolones under Nickel‐catalyzed reaction conditions [158] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 78%
“…[157] A similar type of strategy was reported recently by Zhen et al to access aminoisoquinolines and isoquinolones under Nickel-catalyzed reaction conditions. [158] Liu et al reported the synthesis of 1-difluoroalkylated isoquinolines 144 via Pd-catalyzed radical cascade reactions. [38d] The protocol was witnessed using vinyl isocyanides 28 with bromodifluoroacetates 143 as model substrates.…”
Section: Pd-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
“…Based on the mechanistic investigations and the previous works, 15 a tentative mechanism of these transformations is proposed in Table 4. Firstly, the arylnickel species B is formed between arylboronic acids and Ni( ii )-catalyst A , which coordinates with dinitriles to produce intermediate C .…”
Section: Resultsmentioning
confidence: 98%
“…Nickel, as a 3d transition metal, featuring abundance, inexpensiveness, and low toxicity, has exhibited excellent performance in catalytic reactions. 11 However, examples of nickel-catalyzed nitrile insertion reactions have been limited, 12–15 and there have been no reported examples about the synthesis of multi-substituted pyrazoles and dihydropyridazin-3(2 H )-one skeletons. Motivated by our continued endeavour in nitrile chemistry, 16 we herein report the first example of nickel-catalyzed three component reaction of commercially available malononitrile and butanedinitrile as reactants for the assembly of 1,3-diaryl-1 H -pyrazol-5-amines and 4,5-dihydropyridazin-3(2 H )-ones straightforwardly via an addition, condensation, and annulation sequence of boronic acids and hydrazine hydrochlorides (Scheme 1, eqn (e)).…”
Section: Introductionmentioning
confidence: 99%
“…2-(Cyanomethyl)­benzoic esters have become an important class of building blocks in synthetic chemistry. As shown in Figure , their synthetic applications were highlighted in the construction of various bioactive heterocycles including drug candidates CWJ-a-5 and DCZ0359. A classical method for the synthesis of 2-(cyanomethyl)­benzoic esters is the S N 2 nucleophilic substitution of benzyl halides with highly toxic metal cyanides (Scheme a) .…”
mentioning
confidence: 99%